Principal’s Innovation At MTS Negeri 1 Boyolali: Improving School Quality Though Superior Programs - Natasya, Anas Lutfia; Maksum , Muh. Nur Rochim (Journal of Educational Sciences, 2025)
The quality of Indonesia's education is still low, as reflected in the PISA score. MTs Negeri 1 Boyolali innovates with excellent programs under the leadership of the principal. This study aims to describe the innovations implemented by the principal of MTs Negeri 1 Boyolali in improving the quality of schools through excellent programs and identify the challenges faced in its implementation. This research uses a qualitative method with a phenomenological approach. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman models. The results of the study show that the principal's innovations include improving teacher competence, optimizing facilities and infrastructure, and strengthening community involvement. Excellent programs such as Tahfidz, Science, and Sports contribute to the improvement of students' academic and non-academic achievement. However, its implementation faces challenges, such as limited funding and resistance to change. In conclusion, the innovations implemented have a positive impact on the quality of schools, but still require a more optimal management strategy to overcome existing obstacles.